Predicates in Linguistics as Tools for Analysing the Meaning of Words and Terms - Śliwa, Dorota (Verbum, 2024)
The aim of the article is to underline the predicative character of the meaning of a lexeme and the coherence of the conceptual system underlying (ontological entity) the first meaning of a lexeme (word or term). After distinguishing between meaning and concept, then concept in knowledge engineering and concept in cognitive linguistics based on realist metaphysics, the author presents the Aristotelian predicate as that which expresses at the metalinguistic level the properties of a conceptualised entity of reality. It is characterised by different levels of expression and is linked to ontological structure. An ‘essentialist legacy’ of Aristotle's predicates is realised in essentialist definitions in natural language. They are studied in lexicographic and terminological definitions. The predicates that have their predicative structures in the ontological structure of an entity are illustrated by examples of French and Polish predicates of eagles taken from lexicographical definitions and ornithological terms. They are also used to analyse precisely the metaphors of the parts of an aircraft inherited from the properties of a bird, thus demonstrating the metaphorical conceptualisations specific to each speaking community. The method of analysing the meaning of a word using an Aristotelian predicate makes it possible to separate the ontological level from the level of signifiers, and makes it operational for application to formal language.
Keywords: meaning; concept; Aristotelian predicate; essentialist definition; intrinsic properties; extrinsic properties